Protective immure responses against fatal malarial infection in mice with blood stage malaria vaccin. - Supargiyono Supargiyono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1994)
Studies were carried out to establish suitable infection and immunization method to facilitate investigation on the protective host immune responses against acute malarial infection. Combinations of experimental model using two species of rodent malaria parasites Plasmodium vinckei vinckei and Plasmodium vinckei petteri, two immunization methods were tested, to determine which model are suitable for studying any aspect of host immune responses during protective malarial immunization.The results indicated that the infection of P. v. vinckei and P. v. petteri in LACA or in BALB/c mice generally produce acute and lethal infections. Infection of P.v.vinckei in these experimental models seems more severe than P. v. petteri, and neither intravenous nor intraperitoneal immunization gave significant protection against homologous infection. However, immunization using 108 blood stage parasite P. v. petteri could protect LACA mice from the lethality of homologous challenge, and it seems that cell mediated mechanisms play an important role in host responses against infection. Therefore, P. v. petteri infection in LACA mice and immunization using 10 blood stage parasites given intravenously or intraperitoneally represent a suitable model to study some aspects of host immune response mechanism during malarial immunization.Key Words : Plasmodium vinckei vinckei - Plasmodium vinckei petteri - immune response - cellular immunity - homologous parasites